RETRACTED: An Aberrant Phosphorylation of Amyloid Precursor Protein Tyrosine Regulates Its Trafficking and the Binding to the Clathrin Endocytic Complex in Neural Stem Cells of Alzheimer's Disease Patients - Poulsen, Ebbe T.; Iannuzzi, Filomena; Rasmussen, Helle F.; Maier, Thorsten J.; Enghild, Jan J.; Jørgensen, Arne L.; Matrone, Carmela (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD) is the most common cause of dementia and is likely caused by defective amyloid precursor protein (APP) trafficking and processing in neurons leading to amyloid plaques containing the amyloid-β (Aβ) APP peptide byproducts. Understanding how APP is targeted to selected destinations inside neurons and identifying the mechanisms responsible for the generation of Aβ are thus the keys for the advancement of new therapies. We previously developed a mouse model with a mutation at tyrosine (Tyr) 682 in the C-terminus of APP. This residue is needed for APP to bind to the coating protein Clathrin and to the Clathrin adaptor protein AP2 as well as for the correct APP trafficking and sorting in neurons. By extending these findings to humans, we found that APP binding to Clathrin is decreased in neural stem cells from AD sufferers. APP Tyr hyperphosphorylation alters APP trafficking in AD neurons under the control of Fyn Tyr kinase. We show that compounds affecting Tyr kinase activity and counteracting defects in AD neurons can control APP location and compartmentalization. APP Tyr phosphorylation is thus a potential therapeutic target for AD.